UPAYA MENINGKATKAN PELAYANAN UPTD BENGKEL DKP KOTA SAMARINDA - Umar, Syabran (Jurnal Administrative Reform, 2015)
This study aims to describe and analyze the Governmentsâ€™ effort to improve the service delivered by UPTD Workshop DKP Samarinda and to determine the factors that support and hinder such efforts. The data were obtained from the interviews conducted with technical sources (informants) and key informants (key informant), observation and documentation, which is then analyzed using an interactive analysis model through the stages of data collection, data reduction, data presentation and conclusion.Â